Strumenti online per una verifica preliminare dei Beni Culturali a rischio - Carlucci, Valerio (Archeomatica, 2018)
A brief review of useful online tools for a preliminary verification of Heritage at Risk, developed by international organizations following the affairs of MENA (Middle East and North Africa) since the Arab spring of 2011.